Effects of ferrous iron supplementation on reductive dechlorination of tetrachloroethene and on methanogenic microbial community. Issue 5 (12th May 2021) - Yoshikawa, Miho; Zhang, Ming; Kawabe, Yoshishige; Katayama, Taiki
ABSTRACT: Chloroethenes are common soil and groundwater pollutants. Their dechlorination is impacted by environmental factors, such as the presence of metal ions. We here investigated the effect of ferrous iron on bacterial reductive dechlorination of chloroethenes and on methanogen community. Reductive dechlorination of tetrachloroethene was assayed with a groundwater sample originally containing 6.3 × 10 3 copies mL −1 of Dehalococcoides 16S rRNA gene and 2 mg L −1 of iron. Supplementation with 28 mg L −1 of ferrous iron enhanced the reductive dechlorination of cis -dichloroethene ( cis -DCE) and vinyl chloride in the presence of methanogens. The supplementation shortened the time required for complete dechlorination of 1 mg L −1 of tetrachloroethene to ethene and ethane from 84 to 49 d. Methanogens, such as Candidatus 'Methanogranum', Methanomethylovorans and Methanocorpusculum, were significantly more abundant in iron-supplemented cultures than in non-supplemented cultures ( P < 0.01). Upon methanogen growth inhibition by 2-bromoethanesulfonate and in the absence of iron supplementation, cis -DCE was not dechlorinated. Further, iron supplementation induced 71.3% dechlorination of cis -DCE accompanied by an increase in Dehalococcoides 16S rRNA and dehalogenase vcrA gene copies but not dehalogenase tceA gene copies. These observations highlight the cooperative effect of iron and methanogens on the reductive dechlorination of chloroethenes by Dehalococcoides spp. Abstract : The mechanisms associated with the enhancement of reductive dechlorination of chloroethenes upon ferrous iron supplementation have been examined through a series of laboratory biodegradation tests.